Educación financiera y finanzas personales en estudiantes de contabilidad del noveno y décimo ciclo de la Unap Requena año 2022 - Silva Villacorta, Tesoro (2023)
The objective of this thesis report was to determine the relationship between financial education and personal finances in accounting students of the ninth and tenth cycle of the UNAP Requena, year 2022, where the descriptivecorrelational study and non-experimental design were used, whose population was 79 students, to whom a questionnaire was applied. According to the results obtained, it was determined that financial education in students is rated as average (27%), because sometimes finances help you make better decisions regarding the management of your money; sometimes he ponders the expense to be made on his basic needs; They also consider that sometimes a financial entity manages their money better; and they have almost always chosen to acquire a financial product. For their part, personal finances in students are regular (28%), since they sometimes file all financial documentation, whether physical or virtual; however, they are always aware of your credit debts; but sometimes he takes advantage of the sources of income in a timely manner to make investments; and sometimes have additional sources of income to their main activity. Managing to determine that there is a positive and significant correlation between the variables, corroborated by a coefficient and a significance of (r= 0.760; p=0.000).